Crystal and magnetic structures of Ba4Mn3O10 - Zubkov, V; Tyutyunnik, A; Berger, I; Voronin, V; Bazuev, G; Moore, C; Battle, P (2002)
A polycrystalline sample of Ba4Mn3O10 has been prepared and characterized by X-ray diffraction (290 K), neutron diffraction (290, 80, 5K) and magnetometry (5 ≤ T(K) ≤ 1000). At 290 K the compound is paramagnetic and isostructural with Ba4Ti2PtO10. Mn3O12 trimers, built up from MnO6 octahedra, are linked through common vertices to form corrugated sheets perpendicular to the y-axis of the orthorhombic unit cell (Space group Cmca, a = 5.6850(1), b = 13.1284(1), c = 12.7327(1) Å); Ba atoms occupy the space between the layers. On cooling, the magnetic susceptibility shows a broad maximum at ∼130 K, and a sharp transition at 40 K. Neutron diffraction has shown that long-range antiferromagnetic order is present at 5 K but not at 80 K, although magnetometry at 5K has revealed a remanent magnetization (0.002 μB per Mn) which is below the detection limit of the neutron experiment. © 2002 Elsevier Science (USA).